DAYA HIDUP DAN KUALITAS PERTUMBUHAN TREMBESI (Samanea saman)DANSENGON (Paraserianthes falcataria)PADA MEDIA TANAH BEKAS TAMBANG INTAN DI SHADE HOUSE - Muhammad Subli; Setia Budi Peran; Gusti Syeransyah Rudy (Jurnal Sylva Scienteae, 2020)
Mining activities have the potential to provide substantial regional income. However, these activities also have a negative impact on the environment in the form of damaged land. For this reason, it is necessary to select species that are suitable for local soil conditions and especially fast-growing species, such as trembesi and sengon, which have proven adaptive for mining areas. The purpose of this study is to analyze the percentage of survival and quality of trembesi and sengon plants. The method of research carried out calculates the percentage of life force, life quality and growth of trembesi and sengon plants. Analysis of the data used in this study used a descriptive analysis method by recording or recording the life force and growth quality of two trembesi plants (Samanea saman) and sengon (Paraserianthes falcataria). Percentage of plant life in the medium of ex-mining of diamond trembesi 98% and sengon 92%. The quality of the growth of trembesi and sengon plants in the media of ex diamond mining with the percentage of healthy trembesi plants 96%, unhealthy 0%, languishing 2% and dying 2%. The percentage of healthy sengon plants is 84%, 2% less healthy, 4% languish and 10% die.Keywords: trembesi; sengon; ex diamond mining soil